The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fgene.2022.901827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Exercise on Lipid Metabolism in Rats With NAFLD

Abstract: This work aimed to study the intervention effect of exercise on lipid metabolism in NAFLD rats, provide a more scientific experimental basis for exploring and improving the theoretical system of exercise intervention in NAFLD, and further provide a theoretical research basis for clinical treatment of NAFLD. Forty healthy male Sprague Dawley rats were randomly divided into a blank control group (BC,14) and a model group (MO, 26). After 6°weeks of modeling, the MO group was randomly divided into the model contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The remaining 12 rats in the normal diet group were changed to control group (C), and the high-fat diet group was divided into model group (M) and exercise group (E). E group conducted 8-week exercise intervention with reference to Zhou et al [ 8 ]: 7 d/w, 60 min/t, and 15 m/min ( Figure 1 ). The rats were euthanized at twenty-four hours after the intervention experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 12 rats in the normal diet group were changed to control group (C), and the high-fat diet group was divided into model group (M) and exercise group (E). E group conducted 8-week exercise intervention with reference to Zhou et al [ 8 ]: 7 d/w, 60 min/t, and 15 m/min ( Figure 1 ). The rats were euthanized at twenty-four hours after the intervention experiment.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Studies on the treatment of NAFLD. Many pieces of evidence showed that calorie restriction ( 18 , 19 ), fat restriction ( 20 , 21 ), carbohydrate reduction ( 22 , 23 ), and appropriate vitamin supplementation ( 24 , 25 ) in diet therapy, aerobic exercise ( 26 , 27 ) resistance exercise ( 28 , 29 ) and high-intensity interval training ( 30 ) in exercise therapy had good therapeutic effects. Moreover, clinical experiments have proved that combining diet and exercise may achieve better therapeutic efficacy than a single one ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NAFLD is no longer considered a single process but instead a disease caused by adipose tissue (AT) lipolysis ( 3 , 4 ), gut microbiota ( 5 , 6 ), and liver dysfunction ( 4 ). Moreover, NAFLD is affected by dietary factors, genetic factors, and other factors ( 7 , 8 ). The etiology of NAFLD is still unclear.…”
Section: Introductionmentioning
confidence: 99%